THE EFFECTIVENESS OF USING SPECIAL AEROBIC EXERCISES IN DEVELOPING ENDURANCE PHYSICAL QUALITIES (Scientific journal of the Fergana State University, 2025)
This article is dedicated to studying the effectiveness of using special aerobic exercises in developing endurance physical qualities. It highlights the importance of endurance in improving students' physical and mental health, as well as in enhancing their success in both academic and sports activities.